Uji Gelagat dan Uji Analgesik Ekstrak Etanol Daun Kembang Sungsang (Gloriosa superba L) pada Hewan Coba - Pudjiastuti, Pudjiastuti; Nugroho, Yun Astuti (Jurnal Kefarmasian Indonesia, 2009)
Gloriosa superba L belongs to the Colchiceae family. These vine plants reach 2.5 m in height and can grow at 400 in above sea level. The leaves contain chemical compounds such as alkaloid colchisin, glorisin and triterpen which possess analgesic properties. Many studies have been conducted in the tubers of such plants but scientiﬁc information on the eﬂicacy the leaves as analgesic have not thus far been published. Therefore, in this work a study wa conducted to test behavior and analgesic eﬁicacy of compounds in the Gloria superba L. leaves extracted with ethanol. The results showed the inﬂuence on the central nervous system and analgesic eﬂecls at doses of extract for 2 mg/100g body weight of mice and it's no significant diﬂerent with asetosal (p< 0, 05).